Tyrosine: an efficient natural molecule for copper remediation. Issue 1 (31st March 2015) - Jimenez, Maude; Vandenbossche, Marianne; Dehaese, Amandine; Traisnel, Michel; Casetta, Mathilde
Abstract : Amino acids present a great potential for heavy metals sorption, thanks to their active chemical groups. Tyrosine is an amino acid containing amine, carboxylate and phenol groups and thus is a potential candidate for heavy metals remediation. However, this biomolecule is water soluble, and so it is difficult to remove tyrosine-metal complexes from the water. A potential solution would consist in grafting this biomolecule onto a material to ensure a good separation between heavy metals, trapped by tyrosine-grafted-material, and the water medium. Thus, the grafting of tyrosine onto a polypropylene (PP) nonwoven was carried out. Evidence of the grafting of tyrosine was given by several characterization techniques: Fourier transform infrared spectroscopy and X-ray photoelecron spectroscopy. A 3·2% tyrosine grafting rate was obtained. Then, the sorption efficiency of the tyrosine-functionalized material was evaluated by flame atomic absorption spectrometry. At 20°C and for pH 4·5, approximately 48 mg of copper per gram of PP were trapped, confirming the good efficiency of tyrosine. The most interesting result of this study is the constant sorption capacity whatever the sodium chloride concentration in the copper sulfate solution. This result, specific to tyrosine, allows considering the possibility of the use of such material for marine wastewaters and sediments depollution. This article contains supporting information that will be made available online once the issue is published.